PENGGUNAAN GOOGLE WORKSPACE DALAM MENINGKATKAN PELAYANAN ADMINISTRASI MAHASISWA DI UPT. LABORATORIUM TERPADU UNIVERSITAS SRIWIJAYA INDRALAYA - Muhammad Tri Bakti Utama; Supardi Supardi (Jurnal Ilmiah Administrasi Dan Sosial, 2026)
Student Administration Services at UPT. The Integrated Laboratory of Sriwijaya Indralaya University in handling administrative services has been greatly resolved because it is helped by the existence of an application called Google Workspace where this application helps make work easier but there are problems with  the  system  which  sometimes  the  network  is  unstable  for  the  Head  of  UPT.  Sriwijaya  Indralaya University Integrated Laboratory can provide services using a stable network to improve administrative service processes.The discussion of the problems in this paper is carried out using a qualitative approach with a deductive method which discusses the problems to be studied by writing discussion topics that are describedin general terms and then drawing specific conclusions.Using Google Workspace to Improve Student Administration Services at UPT. Sriwijaya IndralayaUniversity Integrated Laboratory. Student Administration Services in the Integrated Laboratory Section of Sriwijaya  Indralaya  University  can  be  said  to  be  good  by  looking  at  several  indicators,  namely Transparency, Participation, Loyalty, Conditionality and Accountability. Then the Google Workspace Application to Improve Student Administration Services at UPT. The Sriwijaya Indralaya University Integrated Laboratory has had a good impact on Student Administration Services which can be seen from several indicators, namely Flexibility, efficiency, effectiveness, an orderly system and saving funds. Keywords: Use of Google Workspace and Student Administration Services